The Concept of Research on the Development of Economic Clusters in the Agrifood Sector in Poland - Zbigniew NASALSKI (Communications of International Proceedings, 2022)
The aim of the scientific article was an attempt to define an outline of the methodology of research on the use of clusters in the food economy. Organizing and strengthening clusters can be used to strengthen the competitiveness of food economy entities. The concept of research on the development of economic clusters in the agri-food sector in Poland can be modified and adapted to the regional specificity. The development of regional models of cluster connections focused on regional economic goals should be one of the most important implementation goals of modern economic policy, especially in regions with a high concentration of agriculture.
Keywords: economic cluster; food economy; regional development